Exploring genetic susceptibility to obesity through genome functional pathway analysis. Issue 6 (5th May 2017) - Gabrielli, Alexander P.; Manzardo, Ann M.; Butler, Merlin G.
Abstract : Objective: Obesity has been reaching epidemic levels in recent decades, with a growing body of research identifying predisposing genetic components. To explore the relationship of genetic factors contributing to obesity, an analytical computer‐based gene‐profiling approach utilizing an updated list of clinically relevant and known obesity‐related genes was undertaken. Methods: An updated list of 494 genes reportedly associated with obesity was compiled, and the GeneAnalytics profiling software was utilized to interrogate genomic databases from GeneCards® to cross‐reference obesity gene sets against tissues and cells, diseases, genetic pathways, gene ontology (GO)‐biological processes and GO‐molecular functions, phenotypes, and compounds. Results: Obesity‐related fields identified by GeneAnalytics algorithms included 8 diseases, 46 pathways, 62 biological processes, 22 molecular functions, 148 phenotypes, and 286 compounds impacting adipogenesis, signal transduction by G‐protein coupled receptors, and lipid metabolism involving insulin‐related genes ( IGF1, INS, IRS1 ). GO‐biological processes identified feeding behavior, cholesterol metabolic process, and glucose and cholesterol homeostasis pathways, while GO‐molecular processes pertained to receptor binding, affecting glucose homeostasis, body weight, and circulating insulin and triglyceride levels. Conclusions: The gene‐profiling model suggests that pathogenesis of obesity relates to the coordination of biological responses to glucose and intracellular lipids possibly through a disruption of biochemical cascades and cellular signaling arising from affected receptors.